Empowering Muslim Women Micro, Small, and Medium Enterprises (MSMEs) Owners through Working Capital Loan (KUR) - Fitriah, Fitriah; Nurrachmi, Rininta; Ali, Zulkarnain Muhammad (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Background – Financing has been very helpful for women entrepreneurs. Not only it increases income and creates work opportunities, but also eradicates poverty and empowers women financially, socially, psychologically, and politically. Since 2007, Indonesia has provided working capital loan (kredit usaha rakyat or KUR) to assist MSMEs to access finance.Objective - This study aims to analyze the attitude of Muslim women MSMEs owners toward KUR by using Theory of Planned Behavior (TPB).Research Method – The method of data analysis used in this research is Structural Equation Modelling (SEM). Sample of research employed in this study is 100 (one hundred) Muslim women entrepreneurs in food and beverages sector. The data applied in this research is primary data obtained from online and offline survey in Jakarta area.Findings – It is found that the perception of credit ease and service quality influencing the attitude toward KUR application. Meanwhile personal value does not influence the attitude toward KUR application.Practical Implications – The government should put more effort to educate MSME owners to register their business and to produce financial reports and KUR distributors, especially Sharia-compliant KUR, must enhance their service quality to attract more female debtors.